1989
DOI: 10.3758/bf03210712
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal frequency in figure-ground organization

Abstract: Figure-ground organization of an ambiguous pattern can be manipulated by the spatial and temporal frequency content of the two regions ofthe pattern. Controlling for space-averaged luminance and perceived contrast, we tested patterns in which the two regions of the ambiguous pattern contained sine-wave gratings of 8, 4, 1, or 0.5 cycles per degree (cpd) undergoing on:off flicker at the rates of 0, 3.75, 7.5, or 15 Hz. For a full set of combinations of temporal frequency . differences, with each spatial frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
14
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 35 publications
2
14
0
Order By: Relevance
“…The coarse and fine structures of the original shapes should be individually represented in order for the visual system to respond to shapes as quickly as possible with the least number of their features, and to discriminate one shape from others based on the detailed information. Various lines of psychophysical research support that shapes are represented individually by their coarse and fine structures (Inui 1988;Klymenko et al 1989;Sakai and Inui 2002;Victor and Conte 2006); for example, research on face recognition implies that lower spatial frequencies contribute to recognition of whole faces while higher frequencies allow us to understood their detailed shape (Tanaka and Farah 1993;Näsänen 1999). …”
Section: Introductionmentioning
confidence: 99%
“…The coarse and fine structures of the original shapes should be individually represented in order for the visual system to respond to shapes as quickly as possible with the least number of their features, and to discriminate one shape from others based on the detailed information. Various lines of psychophysical research support that shapes are represented individually by their coarse and fine structures (Inui 1988;Klymenko et al 1989;Sakai and Inui 2002;Victor and Conte 2006); for example, research on face recognition implies that lower spatial frequencies contribute to recognition of whole faces while higher frequencies allow us to understood their detailed shape (Tanaka and Farah 1993;Näsänen 1999). …”
Section: Introductionmentioning
confidence: 99%
“…Many factors have been identified that determine whether a region will be perceived as figure or ground. For example, smaller regions are more frequently perceived as figures (Rubin, 1915/1958); regions depicting familiar objects are more likely to be identified as figures (Peterson & Gibson, 1991); regions located in the lower part of a display tend to be perceived as figures (Vecera, Vogel, & Woodman, 2002); spatial frequency in which high spatial frequency regions are perceived as figures (Klymenko & Weisstein, 1986); temporal frequency in which high temporal frequency regions are perceived as figures (Klymenko, Weisstein, Topolski, & Hsieh, 1989; Lee & Blake, 1999); and synchronous motion in which a region containing elements moving synchronously is perceived as a figure (Frost, Wylie, & Wang, 1990; Kandil & Fahle, 2004). …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, activities of these two temporal channels locate the nonflickering region in front and the flickering region behind in depth. Thus, the temporal-frequency content of suprathreshold textures in the adjacent regions reliably and systematically determines their figure-ground organization (Klymenko & Weisstein, 1986;Klymenko, Weisstein, Topolski, & Hsieh, 1989;Wong & Weisstein, 1984, 1985.…”
mentioning
confidence: 99%